EFFECTIVENESS OF LAW ENFORCEMENT CASE BY THE CARTEL COMMISSION HONDA AND YAMAHA BASED ON JUSTICE PANCASILA - Otih Handayani; Juliana S. Ndolu; Achmad Jumeri Pamungkas; Douglas Napitupulu (Jurnal Ius Constituendum, 2020)
This research aims to reconstruct the effectiveness of law enforcement by the Commission in a cartel case Honda and Yamaha justice based on Pancasila. The first reaserch discuss about the effectiveness of the Business Competition Supervisory Commission (KPPU) in law enforcement justice cartel cases Pancasila. Both reconstruct the article in Law No. 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Competition for law enforcement effectiveness. This research is a doctrinal approach of legislation and research . Study shows the first enforcement by the Commission is not operating effectively. The imposition of administrative sanctions from the Commission do not have permanent legal force, where they opened a space for parties reported to object to the level of the Supreme Court (MA). The process to obtain permanent legal force very long whereas 73% of MA won the Commission's decision. Both to achieve effective enforcement, it is necessary to expand the authority of the Commission, which sanctions the administration carried out by the Commission are final or not opened space object. Agae ensure the Commission's decision is fair, then there needs to be a power-sharing within the Commission to establish the field of internal controls.